THE INFLUENCE OF WORD OF MOUNT AND SOCIAL MEDIA ON THE PURCHASE DECISION OF TRADISONAL CAKE (BIKA BAKAR) - Nurlaila Nurlaila; Khairunnisa Butar-Butar; Siti Isma Sari Lubis (Jurnal Ekonomi, 2022)
ng decisions based on a significant value less than 0.05 with t count (3.557) > t table (1.993). This proves that the more promotions through word of mount spread to consumers, the greater the purchase decision. While social media variables on purchasing decisions that there is a partial influence between social media on purchasing decisions are seen based on a significant value less than 0.05 with t count (4,303) > t table (1,993). This proves that the marketing strategy through social media that is carried out will increasingly influence purchasing decisions. Based on these results, the results of the study stated that there was a simultaneous influence between word of mount and social media variables on product purchasing decisions, seen from a significant value of less than 0.05 with an F count (63,522) > F table (3.12). This proves that the better or more frequent promotions through word of mouth and social media are carried out, the greater or increased the product purchasing decision, in this case Bika Bakar Maga.